Impact of Dietary Palmitic Acid on Lipid Metabolism - Murru, Elisabetta; Manca, Claudia; Carta, Gianfranca; Banni, Sebastiano (Frontiers in Nutrition, 2022)
Palmitic acid (PA) is ubiquitously present in dietary fat guaranteeing an average intake of about 20g/d. The relative high requirement and relative content in the human body, accounting for 20–30% of total fatty acids, is justified by its relevant nutritional role. In particular physiological conditions, such as in the fetal stage or in developing brain, the respectively inefficient placental and brain blood barrier transfer of PA strongly induces its endogenous biosynthesis from glucose via de novo lipogenesis (DNL) to secure a tight homeostatic control of PA tissue concentration required to exert its multiple physiological activities. However, pathophysiological conditions (insulin resistance) are characterized by a sustained DNL in the liver, aimed at preventing the excess accumulation of glucose, resulting in increased tissue content of PA and disrupted homeostatic control of its tissue concentration. This leads to an over accumulation of tissue PA resulting in dyslipidemia, increased ectopic fat accumulation and inflammatory tone via toll-like receptor 4. Any change in dietary saturated fatty acids (SFA) usually reflects a complementary change in polyunsaturated fatty acids (PUFA) intake. Since PUFA particularly n-3 highly PUFA, suppress lipogenic gene expression, their intake reduction rather than excess of dietary SFA may promote endogenous PA production via DNL. Thereby the increase in tissue PA and its deleterious consequences from dysregulated DNL can be mistakenly attributed to dietary intake of PA.